A first in human evaluation of a novel contrast media saving device. Issue 6 (4th May 2017) - Sapontis, James; Barron, Garry; Seneviratne, Sujith; Fuernau, Georg; Eitel, Ingo; Ledwoch, Jakob; Thiele, Holger; Saad, Mohammed; de Waha, Suzanne; Poess, Janine; Desch, Steffen
Abstract : Objectives: This study evaluated the usability and contrast volume savings of the novel DyeVert™ System. Background: During coronary diagnostic and interventional procedures, a substantial portion of injected contrast does not contribute to vessel imaging due to reflux into the ascending aorta. Contrast volume is the primary physician modifiable risk factor for prevention of contrast‐induced acute kidney injury CI‐AKI which is a frequent complication in patients undergoing coronary angiographic procedures and is related to increases in morbidity, mortality, and healthcare costs. Methods: In this pilot trial, 44 patients undergoing coronary diagnostic and/or percutaneous coronary intervention (PCI) procedures were enrolled in two centers. All procedures were conducted using a manual manifold injection setup and the DyeVert System, which facilitates the diversion of excess contrast volume prior to injection into the patient. Direct measurements of both the amount of contrast that was attempted to be injected and the actual volume injected into the patient were taken. Results: The difference between the two amounts indicated the volume saved. Procedure types included 34 diagnostic studies and 10 PCI. The mean percent volume saved by the DyeVert System was 47%, with a corresponding P value of <0.0001 achieving the pre‐specified level of greater than 15% of contrast media being saved. Mean volume savings were similar for both diagnostic (47 ± 9%) and PCI (50 ± 9%) procedures. Image quality was good in 43/44 (98%) patients. Conclusions: The DyeVert System substantially decreases contrast delivered to patients during diagnostic or interventional coronary procedures while maintaining adequate image quality. © 2017 Wiley Periodicals, Inc.